2010
DOI: 10.1002/eji.201040298
|View full text |Cite
|
Sign up to set email alerts
|

c‐Rel but not NF‐κB1 is important for T regulatory cell development

Abstract: Regulatory T (Treg) cells are crucial for maintaining peripheral tolerance and controlling T-cell responses. The generation of Treg in the thymus requires TCR triggering and CD28 costimulation. Engagement of these receptors induces a number of signalling pathways, including the activation of NF-jB via PKCh and the Bcl-10/CARMA1/MALT complex. Previous studies have shown that PKCh, Bcl-10 and CARMA1 are important for Treg development. It is unclear, however, whether different members of the NF-jB family contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…In contrast, NF-kB1-deficient mice had relatively normal numbers of these cells [17,19,21], while radiation chimeras reconstituted with RelA/p65-deficient bone marrow cells displayed modest reduction in CD25 1 Foxp3 1 CD4SP thymocyte numbers [19]. The reduced Treg numbers in c-Rel-deficient mice results from a Treg-intrinsic defect rather than from the defective IL-2 production by conventional T cells, because the presence of wild-type cells failed to rescue the impaired Treg development from c-Rel-deficient bone marrow cells in mixed bone marrow chimeras [17,19,21,22]. Moreover, Long et al [20] showed that NF-kB proteins are the mediator that translates TCR signals into Foxp3 transcription in thymocytes, because enhanced NF-kB activity (by transgenic expression of a constitutive active inhibitor of IkB kinase 2) was sufficient for Foxp3 induction in CD4SP thymocytes (and surprisingly in CD8SP thymocytes as well), expressing a monoclonal transgenic TCR that otherwise does not support Foxp3 1 Treg differentiation.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…In contrast, NF-kB1-deficient mice had relatively normal numbers of these cells [17,19,21], while radiation chimeras reconstituted with RelA/p65-deficient bone marrow cells displayed modest reduction in CD25 1 Foxp3 1 CD4SP thymocyte numbers [19]. The reduced Treg numbers in c-Rel-deficient mice results from a Treg-intrinsic defect rather than from the defective IL-2 production by conventional T cells, because the presence of wild-type cells failed to rescue the impaired Treg development from c-Rel-deficient bone marrow cells in mixed bone marrow chimeras [17,19,21,22]. Moreover, Long et al [20] showed that NF-kB proteins are the mediator that translates TCR signals into Foxp3 transcription in thymocytes, because enhanced NF-kB activity (by transgenic expression of a constitutive active inhibitor of IkB kinase 2) was sufficient for Foxp3 induction in CD4SP thymocytes (and surprisingly in CD8SP thymocytes as well), expressing a monoclonal transgenic TCR that otherwise does not support Foxp3 1 Treg differentiation.…”
mentioning
confidence: 90%
“…It has remained unclear, however, which NF-kB family members are required, whether NF-kB proteins directly and/or indirectly regulate the Foxp3 gene, and how they do so. Two reports in this issue of the European Journal of Immunology by Deenick et al [17] and Visekruna et al [18], together with four recent reports published elsewhere [19][20][21][22], have now addressed these issues and suggest that it is c-Rel that pioneers Foxp3 induction and hence Treg differentiation in the thymus.…”
mentioning
confidence: 96%
See 3 more Smart Citations